The Tradition of Larung Sesaji: Social Value And Its Influence on The Lives of Blitar's Coastal Communities - Dewi, Sari; Bashith, Abdul; Amin, Saiful; Kurniawan, Muchammad Akbar; Maulidiah, Linda (IAIN Madura, 2025)
The Larung Sesaji tradition in Blitar's coastal communities has various deep values, including mutual cooperation, togetherness, solidarity, and respect for nature. Besides functioning as a spiritual ritual, this tradition strengthens local cultural identity and creates a harmonious relationship between humans and nature. This research aims to: (1) identify the social values in the Larung Sesaji tradition, (2) analyse its influence on the social life of the community, and (3) explore the challenges in maintaining it in the midst of social change. Using a qualitative approach and a case study in Tambakrejo Village, data were obtained through interviews, observation, and documentation, then analysed using the Miles model. The results showed that the Larung Sesaji tradition fosters togetherness, solidarity, and social justice. In addition, this tradition increases ecological awareness and strengthens the collective identity of the community. However, challenges from modernisation, globalisation and social change, including the declining interest of the younger generation, have the potential to threaten the sustainability of this tradition. To ensure the sustainability of the tradition, innovations involving the younger generation are needed, such as the integration of digital technology and creative approaches in the performance of rituals. Suggestions for future research include analysing 21st century skills, such as critical thinking, creativity, collaboration, and the utilisation of digital technology, to strengthen the role of the Larung Sesaji tradition as part of a cultural heritage that is adaptive to the times